(untitled) (Journal of Organizational Psychology, 2018)
Chronic disease is a national problem that has reached epidemic proportions with serious implications for the workplace. Essentially, the same set of individual health behavior change models have been applied to the treatment of chronic disease despite their inconsistent effectiveness. We examine the potential of Intentional Change Theory (ICT) to improve chronic disease outcomes and thereby contribute a fresh perspective on health behavior change. We review ICT and compare it with five existing theories of individual health behavior change. Our contribution is to articulate the value that ICT can bring to alleviating the effects of chronic disease in the workplace.